Matrix isolation study of methyl propiolate in argon and nitrogen matrices - Lopes, Susy (2020)
Methyl propiolate (HCtriple bondCCOOCH3, MP) isolated in argon and nitrogen matrices was experimentally studied by infrared spectroscopy and by quantum chemical calculations. The calculations, carried out at the DFT(B3LYP) and MP2 levels of theory, predict the existence of two conformers with a planar skeleton. In situ broadband UV light (λ > 200 nm) irradiation of matrix-isolated MP led to the production of new bands ascribed to conformer II testifying the occurrence of the I →II photoisomerization. No other photochemical processes were observed. Assignment of the IR spectra of both conformers is presented, considerably extending the vibrational information available for this molecule hitherto.